STUDY OF MEDICINAL PLANTS DESCRIBED IN DURGA SAPTSATI (AN HOLISTIC ANCIENT TREATISE)- A CRITICAL STUDY (AYUSHDHARA, 2021)
Durgā Śaptaśatī is an important, spiritual and renowned text of Hindu religious scripture describes the glory of Goddess Durgā with deep mysteries and learning's inside it. The beautiful description of this text reveals the trio combination of work-worship and knowledge like the three Mandākinī at one place. In this way, medicinal plants like Padma (Lotus), Akṣa, Bandhūka (Midday Flower), Candana (Sandalwood), Pāṭala (Rose), Kalhāra (Red water lily), Mātuluṇga (Citron) and Pārijāta (Night-flowering coral jasmine) are also described in "Durgā Śaptaśatī". This paper deals with the taxonomic description, medicinal properties and uses of medicinal plants described in Durgā Śaptaśatī.